Opportunities from Metal Organic Frameworks to Develop Porous Carbons Catalysts Involved in Fine Chemical Synthesis - Pérez-Mayoral, Elena (2023)
Funding Information: This work has been supported by Project ref. PID2021-126579OB-C32 from MCIN/AEI/10.13039/501100011033 and Project ref. UFV2023-38 from Universidad Francisco de Vitoria de Madrid. Maria Bernardo thanks FCT (Fundação para a Ciência e Tecnologia) for funding through program DL 57/2016—Norma transitória. Publisher Copyright: © 2023 by the authors.